Polymorphism and expression of the porcine Tenascin C gene associated with meat and carcass quality - A. Kayan (2018)
The research aimed to screen for polymorphism, expression of Tenascin C (TNC) and association with meat and carcass quality traits. Three single nucleotide polymorphisms were detected. In a Duroc×Pietrain F2cross (DuPi) population, g.44488C>T was associated with meat color and ham weight; g.68794A>G was associated with pH at 24h post mortem in ham (pH24H) and muscle area but g.68841C>T was not statistically associated. Genotyping in a commercial Pietrain (Pi) population showed that g.44488C>T was associated with pH24H, whereas g.68794A>G was associated with conductivity at 45min post mortem in loin and backfat thickness. Diplotypes showed significant effects on pH24Hin both populations. The expression was associated with pH at 45min post mortem in loin and cooking loss. TNC was significantly higher in animals with higher muscle pH. Linkage analysis revealed four trans-regulated eQTL on four autosomes. These results suggest that TNC could be a potential candidate gene for meat quality traits in pigs. © 2011 Elsevier Ltd.